Concurrent occurrence of multiple sclerosis and primary CNS lymphoma: a case report - Burgetova, Andrea; Seidl, Zdenek; Vaneckova, Manuela; Jakoubkova, Michaela (Neuro endocrinology letters, 2008)
We present the patient with the diagnosis of multiple sclerosis (MS), relapsing-remitting form with long lasting remission. Unexpectedly, this patient presented dramatical clinical deterioration and revealed clinical symptoms such as bradypsychia, cognitive symptoms, central vestibulare syndrome, spastic quadruparesis. Clinical findings suggested secondary progressive MS, but MRI called in question this diagnosis. The MRI appearance suggested, that MS had been complicated by a different brain pathological lesion, and the brain biopsy was indicated. A histological examination confirmed primary CNS lymphoma (PCNSL). This case exemplifies important aspects of clinical neurology. A re-evaluation of the diagnosis of MS should always be performed in a patient when new symptoms are presented that are unusual or could be due to other pathological processes. MRI offers the highly sensitive way to detect the coexistence of MS and other brain disease. Primary goal of imaging modalities is differential diagnosis between demyelinating diseases, such as MS and other brain lesions. Advanced focus demand contrast- enhancing and mass- effect lesions. It is important to realize, that contrast-enhancement and brain edema may be mitigated by treatment with corticosteroids. In some cases a brain biopsy is needed.
Keywords: dospělí; mužské pohlaví; nádory centrálního nervového systému; Multiple Sclerosis, Relapsing-Remitting; B-buněčný lymfom; nádory mozku; Magnetic Resonance Imaging; Adult; lidé; Lymphoma, B-Cell; Humans; Brain Neoplasms; relabující-remitující roztroušená skleróza; Male; Central Nervous System Neoplasms; magnetická rezonanční tomografie